Discretion in Hiring. Issue 2 (10th October 2017) - Hoffman, Mitchell; Kahn, Lisa B; Li, Danielle
Abstract: Job-testing technologies enable firms to rely less on human judgment when making hiring decisions. Placing more weight on test scores may improve hiring decisions by reducing the influence of human bias or mistakes but may also lead firms to forgo the potentially valuable private information of their managers. We study the introduction of job testing across 15 firms employing low-skilled service sector workers. When faced with similar applicant pools, we find that managers who appear to hire against test recommendations end up with worse average hires. This suggests that managers often overrule test recommendations because they are biased or mistaken, not only because they have superior private information.